STEAM-Based Arabic Language Learning and Madrasah Student’s Critical Thinking - Hasan, Laili Mas Ulliyah; Rodliyah, Nur Aisyatir (Journal of Practice Learning and Educational Development, 2026)
This study aims to examine the implementation of STEAM-based Arabic language learning and its relationship with madrasah students’ critical thinking skills. Arabic language instruction in madrasah contexts is often perceived as teacher-centered and focused on memorization, which limits students’ opportunities to develop higher-order thinking skills. To address this issue, a STEAM-based learning approach was applied to integrate science, technology, engineering, art, and mathematics elements into Arabic language learning activities. This research employed a qualitative descriptive approach conducted at Madrasah Ibtidaiyah Al-Asy’ari. Data were collected through classroom observations, in-depth interviews with teachers and students, and reflective assessments of students’ learning performance. The findings indicate that STEAM-based Arabic language learning encourages active student participation, collaborative problem-solving, and creative language use. Students demonstrated improved critical thinking skills, particularly in analyzing simple problems, expressing ideas in Arabic, and reflecting on learning tasks. The study concludes that integrating STEAM into Arabic language learning is effective in fostering students’ critical thinking and creating a more meaningful and contextual learning experience in madrasah settings.